2017
DOI: 10.1128/jcm.00009-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GenoType NTM-DR Assay for Identification of Mycobacterium chimaera

Abstract: Identification of species within the Mycobacterium avium complex (MAC) is difficult, and most current diagnostic laboratory tests cannot distinguish between species included in the complex. Differentiation of species within the MAC is important, as Mycobacterium chimaera has recently emerged as a major cause of invasive cardiovascular infections following open heart surgery. A new commercial diagnostic assay, GenoType NTM-DR ver. 1.0, is intended to differentiate between three species within the MAC, namely, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The two commercial kitsdINNO-LiPA Mycobacteria and GenoType NTM-DRdcompared well with the reference sequencing, but GenoType Mycobacterium CM and MALDI-TOF MS were not able to sufficiently discriminate M. intracellulare from M. chimaera. These results were in accordance with a recent description of GenoType NTM-DR being tested on 173 MAC isolates from Ireland with a 91% agreement with ITS sequencing [23]. Mass spectrometry was generally disappointing for precise identification of nontuberculous mycobacteria [20,24].…”
Section: Discussionsupporting
confidence: 89%
“…The two commercial kitsdINNO-LiPA Mycobacteria and GenoType NTM-DRdcompared well with the reference sequencing, but GenoType Mycobacterium CM and MALDI-TOF MS were not able to sufficiently discriminate M. intracellulare from M. chimaera. These results were in accordance with a recent description of GenoType NTM-DR being tested on 173 MAC isolates from Ireland with a 91% agreement with ITS sequencing [23]. Mass spectrometry was generally disappointing for precise identification of nontuberculous mycobacteria [20,24].…”
Section: Discussionsupporting
confidence: 89%
“…M. chimaera isolates (n ϭ 87) included an archival collection collected between 2007 and 2017 and more recent clinical and environmental isolates referred from Irish hospitals to the Irish Mycobacteria Reference Laboratory in St. James Hospital, Dublin, Ireland. All isolates were identified by sequencing the 16S rRNA gene and internal transcribed spacer (ITS) region, and a subset of isolates were also identified using the GenoType NTM-DR v1.0 assay (Hain Lifescience), as described previously (42). M. chimaera isolates included for AST were selected on the basis of 1 isolate per patient per year.…”
Section: Methodsmentioning
confidence: 99%
“…Schweickert et al [9] reported that in Germany almost 86% of previously identified species as M. intracelullare are actually M. chimaera. Mok et al [4] reported data from Ireland where 55% of M. intracelullare isolates were misidentified and are actually M. chimaera. Our study showed that M. intracelullare was more often clinically relevant than M. chimaera (29% vs. 6% of clinical isolates, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…During surgeries, HCUs produce aerosols and M. chimaera is dispersed into the air and can colonize the patient. Due to M. chimaera's slowgrowth, it can take even several years after surgery to develop disease [4,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation